2021
DOI: 10.1007/s11242-021-01568-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Reactive Transport Behavior in a Three-Dimensional Discrete Fracture Network

Abstract: models are used to study reactive transport behavior.• We consider the irreversible chemical reaction A + B → C.• Reactions primarily occur in the network backbone and reaction locations are sensitive to chemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…After 10,000 years, the albite in the fast‐flowing fracture dissolves (the fast‐flowing fracture peaks in the histogram disappear because there is no more surface area to compute Da I with) and the reaction moves into dead‐end fractures that are on the boundary between reaction and transport limitation (Figures 5c and 5f). Previous studies have demonstrated that there is advection, albeit slow, in dead‐end fractures within three‐dimensional fracture networks (Hyman, 2020; Kang et al., 2020; Sherman et al., 2021), thus the cells near the entrance to dead‐end fractures can still have faster removal of solute than solute build up. In turn, transport in the disconnected ends of dead‐end fractures is primarily driven by diffusion and reactions are transport limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 10,000 years, the albite in the fast‐flowing fracture dissolves (the fast‐flowing fracture peaks in the histogram disappear because there is no more surface area to compute Da I with) and the reaction moves into dead‐end fractures that are on the boundary between reaction and transport limitation (Figures 5c and 5f). Previous studies have demonstrated that there is advection, albeit slow, in dead‐end fractures within three‐dimensional fracture networks (Hyman, 2020; Kang et al., 2020; Sherman et al., 2021), thus the cells near the entrance to dead‐end fractures can still have faster removal of solute than solute build up. In turn, transport in the disconnected ends of dead‐end fractures is primarily driven by diffusion and reactions are transport limited.…”
Section: Resultsmentioning
confidence: 99%
“…As presented in deep borehole images of the subsurface, weathering proceeds only directly around the fracture (Holbrook et al., 2019). The spatial distribution of weathering in the fracture domain is controlled by the Damköhler number; simple reactive transport simulations involving the reaction A + B → C have demonstrated a similar dependence of the spatial location of reaction with the Damköhler number (Sherman et al., 2021). The importance of the Damköhler number represents the interplay of the physical structure and the resulting hydrologic properties in determining the location and amount of weathering that will occur in the fracture network.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to ECPM, the DFN models offer an accurate description of fluid flow and reactive transfer processes but only within the fractures (Hyman et al., 2015; Molson et al., 2012; Sherman et al., 2021). The Discrete Fracture Matrix (DFM) or hybrid models divide the domain into regions for which an explicit fracture formulation is coupled with a continuum representation of the matrix (Viswanathan et al., 2022), adding more resolution to the description, albeit at the cost of heavier numeric simulations.…”
Section: Introductionmentioning
confidence: 99%